Ethylene‐responsive factor 4 is associated with the desirable rind hardness trait conferring cracking resistance in fresh fruits of watermelon. Issue 4 (6th November 2019) - Liao, Nanqiao; Hu, Zhongyuan; Li, Yingying; Hao, Junfang; Chen, Shuna; Xue, Qin; Ma, Yuyuan; Zhang, Kejia; Mahmoud, Ahmed; Ali, Abid; Malangisha, Guy Kateta; Lyu, Xiaolong; et al.
Summary: Fruit rind plays a pivotal role in alleviating water loss and disease and particularly in cracking resistance as well as the transportability, storability and shelf‐life quality of the fruit. High susceptibility to cracking due to low rind hardness is largely responsible for severe annual yield losses of fresh fruits such as watermelon in the field and during the postharvest process. However, the candidate gene controlling the rind hardness phenotype remains unclear to date. Herein, we report, for the first time, an ethylene‐responsive transcription factor 4 ( ClERF4 ) associated with variation in rind hardness via a combinatory genetic map with bulk segregant analysis (BSA). Strikingly, our fine‐mapping approach revealed an InDel of 11 bp and a neighbouring SNP in the ClERF4 gene on chromosome 10, conferring cracking resistance in F2 populations with variable rind hardness. Furthermore, the concomitant kompetitive/competitive allele‐specific PCR (KASP) genotyping data sets of 104 germplasm accessions strongly supported candidate ClERF4 as a causative gene associated with fruit rind hardness variability. In conclusion, our results provide new insight into the underlying mechanism controlling rind hardness, a desirable trait in fresh fruit. Moreover, the findings will further enable the molecular improvement of fruit cracking resistance in watermelon via precisely targeting the causative gene relevant to rind hardness, ClERF4 .